Initial Geostationary Lightning Mapper Observations. Issue 2 (28th January 2019) - Rudlosky, Scott D.; Goodman, Steven J.; Virts, Katrina S.; Bruning, Eric C.
Abstract: The Geostationary Lightning Mapper (GLM) continuously observes lightning throughout a near‐hemispheric field of view, capturing spatiotemporal variability on unprecedented scales. This study documents GLM lightning distributions during the initial 9 months in the operational Geostationary Operational Environmental Satellite‐East position (December 2017 to August 2018). Spatial maps, summary statistics, and time series illustrate seasonal, regional, and diurnal lightning patterns. Lightning activity shifts from south to north during the study period with most lightning over land (83%). The average GLM flash extends over a 454‐km 2 area, lasts 301 ms, produces 262 fJ of optical energy, and consists of 16.4 (42.2) groups (events). On average, GLM flashes over the oceans are larger (570 km 2 ), of longer duration (345 ms), and brighter (420 fJ) than flashes over land (431 km 2, 293 ms, and 230 fJ). The baseline values and early insights reported herein aim to guide the early development and application of GLM observations. Plain Language Summary: The Geostationary Lightning Mapper (GLM) is the first sensor of its kind, and this technological advancement now allows continuous operational monitoring of total lightning on time and space scales never before available. The GLM has entered into a golden age of lightning observations, which will spur more rapid progress toward synthesis of lightning observations with other meteorological data sets and forecasting tools. This study documents the first 9 months of GLM operations to introduce this new lightning data source and demonstrate the value of this new technology. Within the first 9 months, the GLM captured similar spatial patterns of lightning occurrence to many previous studies covering much longer periods of time. The present study shows that GLM flashes were less common over the oceans, but that the oceanic flashes were larger, brighter, and lasted longer than flashes over land. The ability to continuously sample lightning distributions throughout the GLM field of view allows detailed analysis of the diurnal cycle (e.g., Lake Maracaibo). The GLM presents exciting new possibilities, with countless new applications anticipated over the coming decades. Key Points: The Geostationary Lightning Mapper is a new instrument and the first of its kind to observe lightning from geostationary orbit The GLM is revolutionary in its ability to continuously monitor total lightning distributions throughout its near‐hemispheric field of view GLM flashes are less common over the oceans, but the oceanic flashes are larger, brighter, and last longer than flashes over land